(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this scientific article provides information on the essence of folk crafts and artistic design in technology education, the necessity of teaching, the relevance of the discipline, its problems and important tasks in the development of folk crafts, the connection of folk crafts with national traditions, and its integration with modern crafts.